Tissue culture-induced DNA methylation variation in maize. - Kaeppler, S M (1993)
Twenty-one progeny lines derived from tissue cultures of two embryo sources of maize inbred strain A188 were examined for DNA methylation changes. Total DNA was cut with the isoschizomers Hpa II and Msp I and probed with 18 single-copy Pst I genomic clones and two cDNA clones. Eight of these probes could detect both increases and decreases in methylation. With these probes 39% of the families were found to contain an altered methylation pattern. All changes represented a decrease in methylation. The other 12 probes could detect only increases in methylation; no methylation variation was seen with these probes. Fifteen percent of the methylation changes were homozygous in the original regenerated plant. Changes were stably inherited upon two generations of self-pollination. No sequence variation was observed in Msp I-digested DNA from the same 21 progeny lines. Certain probes detected methylation changes much more often than others. Our study provides evidence that demethylation occurs at a high frequency and could be an important cause of tissue culture-induced variation. Occurrence of the frequent homozygous alterations in original regenerated plants implies a non-random mutational mechanism.